Haemoglobin modulates NO emission and hyponasty under hypoxia-related stress in Arabidopsis thaliana - Hebelstrup, Kim H; van Zanten, Martijn; Mandon, Julien; Voesenek, Laurentius A.C.J; Harren, Frans J. M; Cristescu, Simona M; Møller, Ian M; Mur, Luis A. J (Journal of experimental botany, 2012)
Nitric oxide (NO) and ethylene are signalling molecules that are synthesized in response to oxygen depletion. Non-symbiotic plant haemoglobins (Hbs) have been demonstrated to act in roots under oxygen depletion to scavenge NO. Using Arabidopsis thaliana plants, the online emission of NO or ethylene was directly quantified under normoxia, hypoxia (0.1–1.0% O2), or full anoxia. The production of both gases was increased with reduced expression of either of the Hb genes GLB1 or GLB2, whereas NO emission decreased in plants overexpressing these genes. NO emission in plants with reduced Hb gene expression represented a major loss of nitrogen equivalent to 0.2mM nitrate per 24h under hypoxic conditions. Hb gene expression was greatly enhanced in flooded roots, suggesting induction by reduced oxygen diffusion. The function could be to limit loss of nitrogen under NO emission. NO reacts with thiols to form S-nitrosylated compounds, and it is demonstrated that hypoxia substantially increased the content of S-nitrosylated compounds. A parallel up-regulation of Hb gene expression in the normoxic shoots of the flooded plants may reflect signal transmission from root to shoot via ethylene and a role for Hb in the shoots. Hb gene expression was correlated with ethylene-induced upward leaf movement (hyponastic growth) but not with hypocotyl growth, which was Hb independent. Taken together the data suggest that Hb can influence flood-induced hyponasty via ethylene-dependent and, possibly, ethylene-independent pathways.